(untitled) (Bioscience Journal, 2017)
Breeding genotypes need to be characterized and evaluated in different soil and climatic conditions. There are few studies on association between characters evaluated and their contribution to banana genetic diversity, being essential to guide genetic breeding programs. This study aimed to evaluate the physicochemical characters of banana genotypes, to estimate associations between characters, to determine the relative importance of characters to study on genetic dissimilarity, and to indicate new genotypes to coastal plain region of Sergipe. Fruits from thirteen genotypes were used: Prata (FHIA-18, BRS Platina, PV94-01, BRS Garantida, YB42-47, Pacovan, and Prata Anã), Maçã (BRS Princesa, BRS Tropical, and Maçã), Ibota (Caipira), Gros Michel (Bucaneiro), and Mysore (Thap Maeo). The experimental design was randomized blocks, with thirteen genotypes and three replications. There is physicochemical variability of fruits between genotypes of same genomic group and subgroup, and between hybrids originated from same progenitor. Content of total sugars has greater contribution to genetic diversity among the genotypes, followed by fruit mass and pulp mass, and starch content in two cycles. Associations between fruit length, fruit diameter, and fruit mass and pulp mass in two production cycles based on phenotypic correlation are highly significant. Hybrids FHIA-18, PA94-01, YB42-47, and BRS Tropical, BRS Princesa, and Bucaneiro cultivars are promising for recommendation on coastal plain regions.